Health System Stakeholders' Perspective on the Role of Mobile Health and Its Adoption in the Swiss Health System: Qualitative Study - Lingg, Myriam; Lütschg, Verena (JMIR Publications, 2020)
BackgroundDigital health solutions have great potential to change the way health care is delivered, including better clinical outcomes and improved processes and access to health services. However, the adoption of mobile health (mHealth) solutions for patient monitoring has been rather slow in Switzerland. The reasons are complex, and a better understanding is needed to leverage the full potential of mHealth. ObjectiveThis study aimed to deepen the understanding of the potential relevance and influence of mHealth for the health system and health care provision, and factors influencing its adoption. The findings will be used to provide an outlook on feasible recommendations for action. MethodsWe conducted a qualitative survey using a maximum variation sample of a heterogeneous group of stakeholders (N=50) in the Swiss health care system with a profound knowledge of digital health and medical devices. A semistructured interview guide including open- and closed-ended questions was used to address questions around mHealth relevance and its influence on the health system, the relevance of selected determinants for mHealth adoption, and important influencing factors. A content analysis method was applied. ResultsOverall, respondents thought that mHealth would have a beneficial impact on the Swiss health system but that its adoption would evolve slowly. We derived 23 key opportunities regarding patient and patient pathway, treatment of disease, and diseases and health conditions. High consistency in answers among respondents was observed for treatment of disease. Stakeholders' attitudes toward mHealth adoption along the relevance of 23 preselected determinants were relatively consistent. However, we obtained diverging attitudes regarding the influence of trends, enablers, and restraints in Switzerland and translated them into 26 key themes influencing mHealth adoption. Relevant trends comprise changing needs and expectations of patients, a rising need for efficient health care delivery, growing interest in improved outpatient care, and emerging technologies and progressing digitization. Important enablers include growing demand for new financing schemes and incentive concepts, rising demand for comprehensive information on and stronger body of evidence for mHealth use cases, and increasing need for easy to use alternate care approaches. Challenging restraints are rigidness of thinking and siloed actions of health system actors, complexity of changing the existing regulations and structures, little understanding of mHealth use and the role of clinicians, and risk of further polarization of the population. ConclusionsThis study provides a comprehensive look at mHealth in the Swiss health system. It becomes apparent that strong governance is inevitable to foster a sustainable data strategy and to reconcile the different interests of stakeholders. The use of mHealth will add value but will not necessarily reduce the burden on the system caused by emerging societal needs and changing disease prevalence.